Metode Pengajaran Qira'ah - Beti Mulu (Al-'Adl, 2010)
Reading (qira’ah) is one process to find the language. It can be done directly for the children  (acquisition) to find the first language and can be done consciously for adults whose study the second language by learning formally.            The teaching reading method is the system working to easy application activity which connects the present of the subject to find the meaning of letter in the reading text. The purpose of the reading teaching is to growing and improving the reading skill which consists of: to recognize the Arabic alphabet or letter symbols and to understand the reading content.            In the teaching reading method is appropriated by the kind and the teaching  purpose is the partial method is used to recognize symbols or alphabet Arabic which is can be compound word, and the analysis method is used to understand reading content by several methods like Reading aloud, strategy of random text, reading guide, reading silent etc.